Principal Managerial Competence in Improving Organizational Performance - Murniati, Murniati; Siregar, Fauzan Ahmad (Islamic Educational Management Programme, 2022)
The principal's managerial competence is very important in formal education, because the principal's ability to form a work team in the organization has a very large influence on the quality and quantity of schools, as is the case with the principal of SMP Negeri 1 Simpang Keuramat in improving school organizational performance. As for the formulation of the problem in this study, namely: How the managerial competence of the principal can improve organizational performance at SMP Negeri 1 Simpang Keramat.? Based on the formulation of the problem, the objectives of this study are to determine the managerial competence of the principal that can improve organizational performance at SMP Negeri 1 Simpang Keramat. The research method uses qualitative research with a field research approach (Field Research). In this study, the research subjects were the principal and several members of the school organization. From the results of the study, it was found that the managerial competence of the principal in improving organizational performance through the determination of the vision, mission, and goals, then the existence of an organizational structure or pattern of cooperation by the abilities of organizational members as well as the division of labor and coordination from subordinates to superiors with smooth operation. good communication between fellow members and superiors as well as always making decisions and sustainability is carried out based on valid evidence and the agreement of existing organizational members with other school members, namely educators and education staff.